2020
DOI: 10.1093/ofid/ofaa489
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Novel Colony Stimulating Factor 1 Locus Conferring Susceptibility to Cryptococcosis in Human Immunodeficiency Virus-Infected South Africans

Abstract: Background Cryptococcus is the most common cause of meningitis in HIV-infected Africans. Despite universal exposure, only 5-10% of patients with HIV/AIDS and profound CD4 + T-cell depletion develop disseminated cryptococcosis: host genetic factors may play a role. Prior targeted immunogenetic studies in cryptococcosis have comprised few Africans. Methods We analysed genome-wide SNP genotype data from 524 patients of African d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…This study identified six loci upstream CSF1 gene (encoding for M-CSF) that were significantly associated with the disease susceptibility and validated in a separate cohort. Functional data from RNAseq of human PBMCs stimulated with C. neoformans and in vitro experiments with HIV patient's PBMCs confirmed the crucial role of M-CSF for anti-Cryptococcus host defence mechanisms (134).…”
Section: Moving To Unbiased Genome-wide Approaches To Study Genetics Of Fungal Infectionsmentioning
confidence: 75%
“…This study identified six loci upstream CSF1 gene (encoding for M-CSF) that were significantly associated with the disease susceptibility and validated in a separate cohort. Functional data from RNAseq of human PBMCs stimulated with C. neoformans and in vitro experiments with HIV patient's PBMCs confirmed the crucial role of M-CSF for anti-Cryptococcus host defence mechanisms (134).…”
Section: Moving To Unbiased Genome-wide Approaches To Study Genetics Of Fungal Infectionsmentioning
confidence: 75%
“…rs3804099 T/T was associated with an increased risk of cryptococcal meningitis in HIV-negative patients; rs3804099 C/T was associated with disease severity; rs3804099 was associated with CSF cytokine expression [78] TLR6 valine (V) to methionine (M) missense mutation OR = 1•79 (1•04-3•10); Han Chinese [78] rs3796508 G/A was associated with an increased risk of cryptococcal meningitis in HIV-negative patients [78] TWF2 histidine (H) to histidine synonymous mutation OR = 15•03 (1•74-129•67); Han Chinese [78] rs164637 C/T allele was associated with an increased risk of cryptococcal meningitis in HIV-negative patients [78] TLR9 proline (P) to proline synonymous mutation OR = 1•69 (1•04-2•75); Han Chinese [78] rs352140 T/T was associated with an increased risk of cryptococcal meningitis in HIV-negative patients; rs352140 was associated with CSF cytokine expression [78] systemic lupus erythematosus (SLE), but has a protective function against malaria infection [56,57]. This implies that the threonine substitution increases the risk of autoimmune disease, but is protective against infectious disease, supporting the underrepresentation of the FCGR2B 232I/T genotype in CM patients.…”
Section: Genetic Polymorphisms In Human Immune Signalling Molecules and Susceptibility To Cryptococcal Diseasementioning
confidence: 97%
“…FCGR3B NA2/NA2 is protective against cryptococcosis in HIVnegative patients [46]; There is no association between the FCGR3B NA2/NA2 genotype and cryptococcal meningitis in HIV-negative Han Chinese patients [53] FCGR2B rs11045418 was associated with pulmonary cryptococcosis in HIV-negative patients, but there was no association between the SNP and cryptococcal meningitis [72] -OR = 1•66 (1•13-2•46); Han Chinese [78] rs5743563 T/T was associated with an increased risk of cryptococcal meningitis in HIV-negative patients; rs5743604 C/C was associated with disease severity; rs5743563 was associated with CSF cytokine expression [78] -OR = 1•53 (1•02-2•29); Han Chinese [78] rs5743604 T/T was associated with an increased risk of cryptococcal meningitis in HIV-negative patients [78] TLR2 199 asparagine to asparagine synonymous mutation…”
Section: Genetic Polymorphisms In Human Immune Signalling Molecules and Susceptibility To Cryptococcal Diseasementioning
confidence: 99%
“…Recent genetic studies revealed that the T allele homozygosity at rs6897932 of the L-7R gene (encodes CD127) links to a faster CD4+ T cell recovery after ART initiation, as opposed to CC genotypes in HIV-infected individuals [ 29 , 91 ]. Future genotyping studies of cytokine and cytokine receptor genes may reveal the link between the single nucleotide polymorphism in AIDS patients and predisposition to immune reconstitution disorders, such as IRIS [ 92 , 93 , 94 , 95 ].…”
Section: Immunopathogenesis Of C-irismentioning
confidence: 99%